Fashion and celebrity culture - Gibson, Pamela Church (Berg, 2012)
The interrelationship between fashion and celebrity is now a salient and pervasive feature of the media world. This accessible text presents the first in-depth study of the phenomenon, assessing the degree to which celebrity culture has reshaped the fashion system. Fashion and Celebrity Culture critically examines the history of this relationship from its growth in the nineteenth century to its mutation during the twentieth century to the dramatic changes that have befallen it in the last two decades. It addresses the fashion-celebrity nexus as it plays itself out across mainstream cinema, tel.